Is organic farming a chance for family farms to survive? - Imre Fertő; Csaba Forgács (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
The paper investigates the choice between conventional and organic production technologies for individual farmers in Hungarian agriculture. We employ sequential logit model on a cross-section data set of Hungarian farmers for the period 2007. Our estimations reveal that age of farmers has negative, whilst being full time farmers and having more diversified production structure have positive impact on the intention for being organic farmers. Furthermore, it appears that education, being full time farmers and more diversified production structure positively influence the final decision between conventional and organic farming.
Keywords: 330; innovation; attitudes; organic production; diffusion